Simple Experimental Techniques to Characterize Capacitors in a Wide Range of Frequencies and Temperatures - Amaral, A.M.R.; Cardoso, A.J.M. (IEEE transactions on instrumentation and measurement, 2010)
The aim of this paper is to present two very simple, cheap, and practical experimental techniques that are able to estimate the capacitor equivalent circuit for a wide range of frequencies and temperatures. The capacitor equivalent circuit considerably changes with temperature, aging, and frequency. Therefore, knowledge of their equivalent circuit at their operating conditions can lead to better design proposals. In addition, knowledge of the evolution of the equivalent series resistance (ESR) with temperature is essential for the development of reliable online fault diagnosis techniques. This issue is particularly important for aluminum electrolytic capacitors, since they are the preferred capacitor type in power electronics applications and simultaneously one of the most critical components in such applications. To implement the first technique, it is necessary to put the capacitor under test in series with a resistor and connect it to a sinusoidal voltage. The second technique requires a simple charge-discharge circuit. After acquiring both capacitors' current and voltage through an oscilloscope, which is connected to a PC with Matlab software, it is possible to compute both capacitor capacitance and resistance using the least mean square ( LMS ) algorithm. To simulate the variation of capacitor case temperature, a very simple prototype was used. Several experimental results were obtained to evaluate the accuracy and precision of the two experimental techniques.